Neurological Soft Signs in Aging, Mild Cognitive Impairment, and Alzheimer’s Disease – The Impact of Cognitive Decline and Cognitive Reserve - Urbanowitsch, Nadja; Degen, Christina; Toro, Pablo; Schröder, Johannes (Frontiers in Psychiatry, 2015)
Objectives: Neurological soft signs (NSS), i.e. minor motor and sensory changes, are a common feature in severe psychiatric disorders. We sought to establish the frequency of NSS in patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD) on basis of a large population based sample and to identify their neuropsychological correlates including cognitive reserve. Methods: NSS were examined using an abbreviated version of the Heidelberg NSS Scale in 221 “old” participants born between 1930 and 1932 (63 with MCI, 15 with AD, 143 healthy old controls) and 256 healthy “young” participants (born between 1950 and 1952) of the population-based Interdisciplinary Longitudinal Study of Ageing (ILSE). Subjects received thorough neuropsychological testing; years of school education were used as a proxy for cognitive reserve. Results: NSS scores were significantly (p<0.001) higher in the AD patients (5.6±3.11) than in the healthy old controls (2.8±1.90) and in the MCI patients (3.0±1.96). This result was confirmed after years of school education which were inversely correlated (r = - 0.25; p<0.001) with NSS were entered as a covariate. In the patients but not in the controls, NSS were significantly correlated with deficits in executive functioning and visuospatial functioning. Comparison of NSS scores between “old” (2.84 ± 1.9) and “young” (2.46 ± 1.97) controls yielded only minor, non-significant differences after education (13.86 ± 3.0 vs. 14.61 ± 2.48 years, respectively) was controlled for. Conclusions: Our results demonstrate that NSS are frequently found in mild AD but not in MCI. NSS refer to frontal-executive deficits and visuospatial dysfunction rather than age per se and can be partly compensated for by cognitive reserve.